CASE REPORT ON EPIDERMOLYSIS BULLOSA- A RARE DISORDERS - Gottimuukula, Dileepreddy; Chakinala, Rakesh; Kagithapu, Surender; Morishetty, Yogi; Puchchakayala, Goverdhan (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2016)
Epidermolysis bullosa is a rare group of skin disorders which is characterized by extreme fragility of skin and mucous memberane, which leads to formation of blisters and skin lesions. It affects 1 out of every 50,000 live births. There is no specific treatment, daily wound care and pain management are the only available treatment options. Here we report a case of male neonate with epidermolysis bullosa and respiratory distress. The neonate was died due to severe respiratory distress.